Caracterização físico-química de filmes finos de ftalocianinas metálicas - Scheidt, Wanessa Fernanda (2018)
The search for new materials with physicochemical properties for use in devices and sensors are reasons for the study of metal phthalocyanines. Phthalocyanines are highly conjugated macrocyclic compounds of blue or green color and high thermal and chemical stability. They are very used in the formation of fine films well ordered by the casting method. Generally, phthalocyanines exhibit ptype semiconductor properties, but substitutions in their peripheral rings may alter this n-type semiconductivity. Fluorinated phthalocyanines have presented films with good molecular organization, attracting attention to study in solar cells. This work deals with the formation of thin films, using the casting technique, of zinc hexadecafluorophthalocyanines (F16ZnPc) and cadmium (F16CdPc), and the investigation of crystallinity in these films. The objectives of the work were: to analyze the solubility of the compounds the solubility of the compounds in volatile organic solvents; prepare thin films on glass substrates coated with fluorine-doped tin oxide (FTO) and characterize them before and after the heating. Absorption spectroscopy in the ultraviolet-visible (UV-Vis.) region, for solutions of these compounds, have shown that the solvent may influence the observation of the monomeric or dimeric forms. The films show spectra with wider bands and formation of type J aggregates. Changes observed after the heat treatment, carried out at 300 oC for 3 h, suggest the reordering of the molecules on the substrates. Atomic force microscopy (AFM) images showed that there was an elongated preferential arrangement in F16CdPc films and some loss of material for F16ZnPc. Scanning electron microscopy (SEM) crystallites were observed for F16CdPc, but few changes have been observed for F16ZnPc. X-ray diffraction (XRD) results revealed crystalline films, where rings could have different orientations on the substrate. However, after heating, they may have adopted a single orientation, called face on, where the molecules would be in a horizontal position in relation to the substrate.